PELATIHAN TEKNIK ”HANDS ON” DENGAN POSISI ERGONOMI UNTUK MENINGKATKAN KETERAMPILAN DAN PELAYANAN CAREGIVER STROKE INFORMAL - Heltty, Heltty; Lisnawati, Lisnawati; Saptaputra, Syawal Kamiluddin (Jurnal Abdi Insani, 2024)
The modern lifestyle of the people of Kendari City can have an impact on health, especially stroke. The healing process for stroke patients is a long process so it requires the role of the family as caregivers. Lack of caregiver knowledge and skills in caring for post-stroke patients at home can create a burden for caregivers. Caregivers have never received education and training on how to lift and move (hands-on) family members after a stroke. The aim of Hands-on technique training with ergonomic positions was to increase the knowledge and skills of caregivers, which in the end can contribute to reducing the burden, including the cost of post-stroke care, and improving the quality of health services in the community. The method of implementing this training includes providing education, demonstrations and mentoring. The pre-test and post-test were carried out before and after the training. As a result of this community service, there was an increase in the knowledge of caregivers and health cadres by 31% and increased skills in applying hands-on techniques with ergonomic positions. The results of observations during the re-demonstration showed that the participants were able to repeat the skills that had been taught well. Good knowledge and skills make it easier for stroke caregivers to play an active role in the recovery process of stroke patients at home. The knowledge gained from this training can be used by caregivers in caring for family members after stroke without complaints of fatigue. Health cadres can also utilize the knowledge and skills gained during this training activity by teaching other caregivers who have not participated in this training activity. The Hands-on technique training activities with ergonomic positions that have been implemented provide new knowledge and improve the skills of informal stroke caregivers and health cadres. This increase can improve the quality of public health services.